Strategic management and its influence on the economic and financial situation of the Mypes in the hardware sector of the Jesús María district, in times of pandemic: Gestión estratégica y su influencia en la situación económica y financiera de las Mypes del sector ferretero del distrito de Jesús María, en época de pandemia - Ore Olivera, Norman Raul (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2024)
The objective of this research was to determine the relationship between strategic management and the economic and financial situation of micro and small enterprises (MSEs) in the hardware sector of the Jesús María district during the COVID-19 pandemic in the period 2020-2021. A quantitative approach and correlational scope were used, with a sample of 26 MSEs and the data collection technique was a survey. The results showed a very high positive correlation between strategic management and the economic and financial situation, supporting the importance of strategic management in the competitiveness and economic development of MSEs. It was concluded that strategic formulation, strategic execution, and strategic control are also related to the economic and financial situation of MSEs. These conclusions have significant implications for companies in the hardware sector, as they highlight the importance of effective strategic management in times of crisis. The findings support the need to plan, execute, and control strategies to face economic and financial challenges.